RESHAPING FUTURE SKILLS OF PROFESSIONAL ACCOUNTANTS - Alfonsa Dian Sumarna (Universitas Multimedia Nusantara, 2020)
Acceleration change of global economy causes accounting profession require to have knowledges, skills, and abilities that can support company’s sustainability growth and able to compete nationally and internationally. The accounting profession in the future cannot be a solitery skill but must adapt and evolve in line with new emerging technology. In this research, we using descriptive qualitative research, to explore in depth a review of the factors that influence the accounting profession in the future due to the evolution and revolution of information technology. This research explores information using narrative perspective to understand the implications of modern technology, the drivers of change in the accounting profession, and the future needed of accountant’s skills in accounting work area such as audit and assurance; corporate reporting; financial management; strategic planning and performance management; tax; and governance, risk, and ethics. The needed of competence in analytical and communication skills, knowledge of software and big data, holistic knowledge of internal business, local and global trends are important things that need attention for profesional accountants. Technical skills and ethics (TEQ) and behavior take the prominent role to be able to adapt to changing professional needed. . Keywords: Professional Accountant, Information Technology, Competency, Accounting